The Effectiveness of a Health Literacy Development Program in Coronavirus 2019 Prevention for High-risk Persons with HIV Infection - Satjeenphong, Punjamarpon; Moolsart, Sutteeporn; Uthis, Penpaktr (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research was a two-group pretest-posttest design. The purposes of the research were to study the effects of a health literacy development program in Coronavirus 2019 prevention for high-risk persons with Human Immunodeficiency Virus (hereafter “people with HIV” or PWH) on their health literacy and their Coronavirus 2019 preventive behavior.The samples were PWH who came to receive services at the HIV clinic of Pathum Thani Hospital. The sample was selected by Purposive sampling and put into an experimental group and a comparative group with 32 persons each. The program was based on the concept of health literacy development for PWH contributed by the National Association of People with HIV in Australia. The 6-week program activities. Research instruments were 1) a health literacy development program in Coronavirus 2019 prevention for the high-risk group of PWH. 2) a handbook of health literacy in Coronavirus 2019 prevention. 3) Questionnaires on health literacy and Coronavirus 2019 preventive behavior. The content validity indexes were .95 and 1.00, respectively. Cronbach’s alpha coefficient of the Coronavirus 2019 were .85 and .83, respectively. Data were analyzed by descriptive statistics and a t-test. The result revealed as follows: after enrolling in the program, the health literacy and preventive behavior in Coronavirus 2019 prevention of the experimental group was better than before enrolling in the program and better than the comparative group to a statistically significant degree at p-value < .05